PENYEBAB KEMUNDURAN PERADABAN ISLAM PADA ABAD KLASIK - SYAMRUDDIN NASUTION (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2017)
This article examines the history of Islam who suffered a setback in the classic century in particular on three namely Daulah is Daulah Abbasiyah in Baghdad, Daulah Umaiyah in Spanyol and Daulah Fatimiyah in Mesir, whereas before ever experiencing a renaissance that quite fascinating, with the causes setbacks a different. Article using a method description and content analysis there are three mentioned above Daulah to discover the cause of their retreat. The study finds that the causes of the setback in the three Daulah, in Baghdad caused conflict Khalifah with Amir Umara, Khulaqu Khan is coming crush Baghdad including killing both. In Daulah Umaiyah Spanyol cause internal conflict among Muslims caused the kings of classes and the next Christians come up against them by giving them a choice between the two; leaving of Spanyol or convert to cristiany in Daulah Fatimiyah cause conflict Khalifah with the people caused imposition Syi’ah to the population moyority Sunni. It can be used as guidelines in an effort to avoid the causes of conflict in Indonesia to prevent setbacks of civilization and science as mentioned above.